Using Sensewear armband and diet journal to promote adolescents' energy balance knowledge and motivation - Senlin Chen; Xihe Zhu; Gregory J. Welk; Youngwon Kim; Jungmin Lee; Nathan F. Meier (Elsevier, 2014)
Purpose: Educating adolescents about energy balance (EB) is essential for effective weight control. This study utilized the Sensewear (SWA) armband and a diet journal to promote adolescents' EB knowledge and motivation. Methods: Ninety sixth graders were randomly assigned into the experimental group (n = 46) who utilized SWA and diet journal for 7 consecutive days or the control group (n = 44) who did not. Both groups were pre- and post-measured on EB knowledge, situational interest, and weight. The experimental group was tracked on motivation effort, energy expenditure (EE), and energy intake (EI). Results: EB knowledge significantly increased and situational interest remained stable (except for total interest and enjoyment) over time, but these changes did not favor the experimental group. Situational interest and motivation effort were correlated with EE, EI, and/or EB. Conclusion: Tracking EB using the SWA and diet journal is motivating but has limited efficacy in promoting adolescents' EB knowledge. Using these two tools as educational technology in conjunction with a focused, systematic, and educational approach has the potential to leverage adolescents' EB knowledge, motivation, as well as behaviors for living an energy-balanced lifestyle.